Integration of Aesthetic Medicine into Modern Dental Practice - Rafałowska, Julia; Sajda, Małgorzata; Sikora, Maria; Sikora, Gabriela; Wnuk, Beata; Śledź, Katarzyna; Piórkowski, Jakub; Grygołowicz, Julia; Salloum, Sara; Zalewska, Klaudyna; et al. (Quality in Sport, 2026)
Introduction: Modern aesthetic dentistry increasingly integrates techniques from aesthetic medicine to improve the appearance and function of the oral cavity. Growing patient expectations concerning not only health but also the aesthetics of teeth and perioral tissues have led to the development of interdisciplinary treatment methods. Materials and Methods: This article reviews current techniques used in aesthetic medicine, such as botulinum toxin, tissue fillers, and mesotherapy, and their adaptation in dental practice. The use of platelet-rich plasma (PRP) for aesthetic treatment of the face and perioral structures is also discussed. Results and Discussion: Aesthetic dentistry now includes procedures that enhance both teeth and facial soft tissue aesthetics. Botulinum toxin is used to treat gummy smile, bruxism, and muscular asymmetry. Dermal fillers help in contouring facial structures and enhancing lip volume. Mesotherapy and PRP support tissue regeneration and skin quality, also aiding healing after dental procedures.